Facial Pressure Ulcers in a COVID-19 50-year-old Female Intubated Patient - Zingarelli, Enrico M.; Ghiglione, Marco; Pesce, Marianna; Orejuela, Ileana; Scarrone, Silvia; Panizza, Renzo (Indian Journal of Plastic Surgery, 2020)
In case of severe acute respiratory distress syndrome (ARDS), as in coronavirus disease 2019 (COVID-19) affected patients, the invasive ventilation in prone position can improve the prognosis, albeit with an increased risk of facial pressure ulcers. In this report, we will relate a case of facial pressure ulcers in a SARS-CoV-2 positive 50 year-old woman with the aim to describe the high-complexity management of COVID 19 in which healthcare professionals across the world are still involved.
Keywords: SARS-CoV-2; Covid-19; facial pressure ulcers